Understanding self-regulated learning in Singapore's social studies classrooms. (2nd January 2022) - Lim, Seo Hong; Baildon, Mark
ABSTRACT: Self-regulated learning, reflective thinking, and meta-cognition have been given greater emphasis in Singapore's education system as central to the development of 21 st century competencies and lifelong learning capacities. This study explores students' perceptions of their Self-Regulated Learning (SRL) strategies in Secondary Social Studies after engaging in a Computer-Based Learning Environment (CBLE) lesson with online information sources. Semi-structured group interviews were used to tease out the SRL strategies utilised by students from two different schools. SRL strategies were embedded in the CBLE as instructional prompts created for the purpose of assisting students during task completion. Students were then asked to reflect and comment on their work to identify SRL strategies they utilised in their learning. Findings demonstrate a range of SRL behaviours conveyed by students in the areas of planning for learning tasks, monitoring their learning, and reflection on their learning. The study highlights the importance of SRL strategies in Social Studies education to improve student learning.